How to Revitalize Infrastructure Investments in Brazil : Public Policies for Better Private Participation, Volume 1. Main Report - World Bank (Washington, DC, 2012)
Amid a shifting policymaking environment from private to public, volume one of this report discusses how public policies could attract more and better private investments. In attracting back private capital, this report argues that Brazil must do three things. First, it must eliminate remaining regulatory bottlenecks and policy uncertainties in selected sectors. Secondly, design infrastructure concessions to avoid "excessive" renegotiations while simultaneously guaranteeing an adequate rate of return for investors and protecting consumers' welfare. And finally, strengthen the quality of the regulators for technically sound and coherent decision-making processes. Volume two is the background report and looks at infrastructure statistics in Brazil and international benchmarks, regulatory policy issues, contract negotiations, and gives conclusions and policy implications on these topics.